Contribution to Research on Male Victims of Domestic Violence - Knežić, Branislava (Zbornik Instituta za kriminološka i sociološka istraživanja, 2010)
During the last twenty years, the number of research studies on family violence, and especially violence against women and children, has increased, while research on male victims of domestic violence is marginalised. Prevention of family violence demands studies that will enlighten all relevant aspects of the problem and will also give holistic insight into the specificities and circumstances of violence between family members. This text is a small attempt to point out the importance and need for research of this phenomenon as a whole, including both genders. The reason for that approach is also based on the presented cases of violence against men in the family. Since we are discussing a phenomenon that is not sufficiently explored, the researcher should follow the road of "discovery" by application of the qualitative method, trying to "reach" complex and subtle relations in the family and social environment.